2013
DOI: 10.1186/1824-7288-39-75
|View full text |Cite
|
Sign up to set email alerts
|

Pidotimod: the past and the present

Abstract: At the end of 1990s, acute respiratory tract infections (ARTIs) were called the 'forgotten pandemic’, with a clear dichotomy between developing and industrialised countries in mortality and morbidity, the main outcomes associated with ARTIs. This definition still applies 20 years later, when the introduction of new and safe antibiotics and vaccines has certainly contributed to controlling the most life-threatening ARTIs, but has not had a major impact on viral ARTIs in paediatric age. One functional approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Pidotimod has shown an excellent profile of tolerability and safety in addition to a significant effectiveness in modulating immune response and in controlling RRI [ 24 – 26 ]. In vivo and in vitro studies showed that Pidotimod could improve immune response, affecting both adaptive both innate immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Pidotimod has shown an excellent profile of tolerability and safety in addition to a significant effectiveness in modulating immune response and in controlling RRI [ 24 – 26 ]. In vivo and in vitro studies showed that Pidotimod could improve immune response, affecting both adaptive both innate immunity.…”
Section: Discussionmentioning
confidence: 99%
“… Pidotimod Among immunomodulators, Pidotimod is a synthetic dipeptide molecule endowed with immunomodulatory activity that affects both innate and adaptive immune responses. Previous positive effects on inflammation were obtained in in vitro studies [ 51 , 52 ]; and subsequently in in vivo studies, where the drug reduced the incidence of upper and lower airways symptoms in children [ 53 ], and augmented the influenza specific immune responses in patients with Down syndrome who underwent vaccination [ 54 ]. Lastly, a recent multicenter, interventional, prospective study was conducted on adult patients hospitalized with community acquired pneumonia [ 55 ].…”
Section: Recommendations With Lower Evidence and Analysis Of Studies mentioning
confidence: 99%
“…In the last years different kinds of immunostimulants of natural or synthetic origins and working with different mechanisms have been created for the prevention of ARTIs. Pidotimod (3-L-pyroglutamyl-L-thiaziolidine-4 carboxylic acid) is a synthetic dipeptide molecule with immunomodulatory properties [ 1 ].…”
Section: Reviewmentioning
confidence: 99%
“…The results show benefits from that therapy in many aspects of respiratory tract infections: a reduction of the number of infections, less day of fever, a lesser severity of signs and symptoms, and consequently a reduction in use of antibiotics and symptomatic drugs. Furthermore, the trials suggest that Pidotimod is a simple, well-tolerated and safe approach to reduce risks and symptoms correlated to respiratory tract infections [ 1 ] (Table 1 ).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation